Perception of Indian physiotherapists about awards: a survey - Mehta, Ruchi; Chaudhari, Priyanka; Khatri, Subhash M. (International Journal Of Community Medicine And Public Health, 2019)
Background: World has become more awards centric probably because of the desire to recognize achievement is an integral part of being human. Awards and trophies are big business in 21st century and they are given to people of all ages by all kind of organizations. Physiotherapy profession has a long history of awards all over the globe but the current status of physiotherapy awards in India is hardly studied, documented or published in recent times and hence to get an insight of the same this survey research was done by inviting physiotherapy professionals with varying work experience, professional qualifications and achievements across the country. Methods: A qualitative research approach was used to conduct an online survey of physiotherapists in India. A brief questionnaire with basic information and strategic questions about awards and perception of physiotherapists were used for this purpose. Results: Informants reported that there hardly any award given by government to recognize the contribution of physiotherapists to the society. Most of they believed that it’s because of lack of political will and absence of central regulatory authority or council for physiotherapy profession in India. Most of them were happy about the award given by nongovernmental organizations but were not satisfied with its credibility, transparency in the process and selection of winners and felt mostly it’s a biased practice. Conclusions: There is need for some sort of awards and recognition of physiotherapists’ contribution to health care and the society by government and the process of selection for some nongovernmental awards need to be more transparent and unbiased.